USING OF BYOD MODEL FOR TESTING OF EDUCATIONAL ACHIEVEMENTS ON THE BASIS OF GOOGLE SEARCH SERVICES (Journal of Information Technologies in Education (ITE), 2016)
The technology of using their own mobile devices of learners for testing educational achievements, based on the model of BYOD, in an article is offered. The proposed technology is based on cloud services Google. This technology provides a comprehensive support of testing system: creating appropriate forms, storing the results in cloud storage, processing test results and management of testing system through the use of Google-Calendar. A number of software products based on cloud technologies that allow using BYOD model for testing of educational achievement are described, their strengths and weaknesses are identified. This article also describes the stages of the testing process of the academic achievements of students on the basis of Google search services with using the BYOD model. The proposed approaches to the testing of educational achievements based on using of BYOD model extends the space and time of the testing, makes the test procedure more flexible and systematically, adds to the procedure for testing the elements of a computer game. BYOD model opens up broad prospects for implementation of ICT in all forms of learning process, and particularly in testing of educational achievement in view of the limited computing resources in education.
Keywords: knowledge control; computer testing of educational achievements; cloud technologies; cloud services of search service Google; model BYOD; updated knowledge; quest